2015
DOI: 10.1016/j.jpowsour.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural manipulation approaches towards enhanced sodium ionic conductivity in Na-rich antiperovskites

Abstract: h i g h l i g h t s g r a p h i c a l a b s t r a c tA series of Na-rich antiperovskites were developed as advanced solid electrolytes.The materials are nonflammable, low-cost and suitable for thermoplastic processing. Enhanced sodium ionic conductivity was achieved by structural manipulation approaches. The Na ionic conductivity of Na 2.9 Sr 0.05 OBr 0.6 I 0.4 reaches 1.9 Â 10 À3 S/cm at 200 C. a b s t r a c tHigh-performance solid electrolytes are critical for realizing all-solid-state batteries with enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(190 citation statements)
references
References 27 publications
11
174
4
1
Order By: Relevance
“…To our knowledge, the melting temperature of Na 3 OBr is reported to be about 255 °C . Another work indicates that Na 3 OBr can be synthesized via solid‐state reaction at about 450 °C .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, the melting temperature of Na 3 OBr is reported to be about 255 °C . Another work indicates that Na 3 OBr can be synthesized via solid‐state reaction at about 450 °C .…”
Section: Resultsmentioning
confidence: 94%
“…In 2013, Ramanna et al studied its structural, elastic, electronic, and optical properties using two different density functional methods within generalized gradient approximation. In 2015, Wang et al tried to improve Na + conductivity in Na 3 OBr by chemical manipulation techniques. In 2016, Zhu et al studied the transport mechanism of Na ions and found that they transport between the nearest Na ions in the NaO 6 octahedra.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhu et al 46 analyzed their Naion transport mechanisms and reported low ionic conductivities (s z 10 À8 S cm À1 at RT, activation energy E a ¼ 0.6-0.7 eV). Nonetheless, chemical modications leave substantial room for improvement, e.g., by aliovalent substitution the conductivity of Na 2.9 Sr 0.05 OBr 0.6 I 0.4 reaches 0.19 mS cm À1 at 200 C. 47 Other oxides such as Na 2 SO 4 , Na 3 PO 4 , and Na 4 SiO 4 , are generally characterized by low ionic conductivity. However, they can be used as coating materials or end-members of better performing electrolyte solid-solutions such as Na 2 SO 4 / Na 4 SiO 4 , 48 Na 3 PO 4 /Na 2 SO 4 , 49,50 Na 3 AlF 6 /Na 2 SO 4 , 50 and Na 3 PO 4 / Na 4 SiO 4 .…”
Section: Materials Selectionmentioning
confidence: 99%
“…Larger Na + ions are better for stabilizing the antiperovskite structure, and hence, more NaRAPs are expected. In the solid solution Na 3 OX (X = Cl, Br, I), lattice mismatch and nonequivalent‐doping strategies have been successfully adopted to promote the performance . The optimized Na 2.9 Sr 0.05 OBr 0.6 I 0.4 exhibits a conductivity beyond 10 −2 S cm −1 when approaching the melting point.…”
Section: Emerging Functionalities Of Antiperovskitesmentioning
confidence: 99%